Concrescence of the right maxillary second and third molars: A case report - Yan Xu; Jin Sun (Clinical Case Reports, 2022)
Abstract Herein, we reported a rare case of concrescence of #17 and #18, including the clinical and imaging findings. After extracting the concrescence, the fistula on #17 gradually disappeared. In addition, we analyzed the histological etiology and clinical diagnosis and treatment of concrescence from the sight of periodontal functional stimulation.